Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China - Yao, Min; He, You; Peng, Zuo-Gang (Zootaxa, 2018)
Lanlabeo, a new genus of fish belonging to the family Cyprinidae, is described from the Pearl River drainage basin in Guangxi Province, southern China. This new genus is distinguished from all other genera of the cyprinid tribe Labeonini by a combination of morphological and phylogenetic characters. It differs morphologically from all other Asian labeonins in its uniquely modified oromandibular morphology. For example, this genus has a frenum connecting the upper jaw and lower lip at the corner of the mouth, regularly arranged papillae densely scattered over the ventral margin of the rostral cap, a vestigial upper lip, a rostral cap overlying the upper jaw and with a fimbriate posterior margin, and a lower lip divided into two lateral fleshy lobes and one central plate. These two lateral fleshy lobes are small and translucent, and the median lobe of the lower lip is large and has papillae regularly arranged in many transverse rows. In the lower jaw, the dentary is transversely L-shaped in ventral view because its anterior part forms a right-angle turn and its transverse branch is anterioposteriorly expanded. In addition, analyses of four nuclear gene datasets indicate that this new genus forms a highly divergent lineage within the Labeonini, and that Lanlabeo is closely related to the genus Ptychidio. Therefore, based on morphometric differences and phylogenetic relationships, we describe this new genus herein as Lanlabeo, containing the new species Lanlabeo duanensis.